Toll-Like Receptor 9 Promotes Cardiac Inflammation and Heart Failure during Polymicrobial Sepsis - Ralph Lohner; Markus Schwederski; Carolin Narath; Johanna Klein; Georg D. Duerr; Alexandra Torno; Pascal Knuefermann; Andreas Hoeft; Georg Baumgarten; Rainer Meyer; Olaf Boehm (Mediators of Inflammation)
Background. Aim was to elucidate the role of toll-like receptor 9 (TLR9) in cardiac inflammation and septic heart failure in a murine model of polymicrobial sepsis. Methods. Sepsis was induced via colon ascendens stent peritonitis (CASP) in C57BL/6 wild-type (WT) and TLR9-deficient (TLR9-D) mice. Bacterial load in the peritoneal cavity and cardiac expression of inflammatory mediators were determined at 6, 12, 18, 24, and 36 h. Eighteen hours after CASP cardiac function was monitored in vivo. Sarcomere length of isolated cardiomyocytes was measured at 0.5 to 10 Hz after incubation with heat-inactivated bacteria. Results. CASP led to continuous release of bacteria into the peritoneal cavity, an increase of cytokines, and differential regulation of receptors of innate immunity in the heart. Eighteen hours after CASP WT mice developed septic heart failure characterised by reduction of end-systolic pressure, stroke volume, cardiac output, and parameters of contractility. This coincided with reduced cardiomyocyte sarcomere shortening. TLR9 deficiency resulted in significant reduction of cardiac inflammation and a sustained heart function. This was consistent with reduced mortality in TLR9-D compared to WT mice. Conclusions. In polymicrobial sepsis TLR9 signalling is pivotal to cardiac inflammation and septic heart failure.